Economics of Beef Cattle Fattening Business in Different Environmental Areas in South Konawe Regency, Southeast Sulawesi Province - Alwi, La Ode; Iswandi, R. Marsuki; Gafaruddin, Abdul; Zani, Munirwan; Sudarmo, Hadi; Satrah, Vit Neru (Jurnal Ilmu dan Teknologi Peternakan Tropis, 2023)
This study aims to determine the profile of livestock and explore sustainable incomes for beef cattle fattening farmers with the location of the agricultural area and the Tempeh Factory area in Konda Sub-district, South Konawe, Southeast Sulawesi. Data retrieval was used the Participatory Rural Appraisal (PRA) method, which was an approach that involves family members or individuals to analyze the reality of the living conditions they run. This study involved 45 farmers who were selected by purposive sampling based on five considerations. The analytical model used to test the differences between the two locations wasthe independent T-test analysis. The results showed that the age of the breeder, the experience of raising livestock, the number of family dependents, and the number of livestock ownership were not significantly different (p>0.05) from the two research locations. The motivation for raising livestock as savings and functions as fertilizer was not significantly different in the two locations, but the motivation for livestock as the main source of income showed that the area of agricultural location was higher than that of the Forging Factory (P